166 Air emissions from swine industrial livestock operations and sleep among residents in nearby residential communities. (3rd May 2021) - Jackson, Chandra; MacNell, Nathaniel; Heaney, Christopher
Abstract: Introduction: Waste from swine industrial livestock operations (ILOs) produces air pollutants that have been associated with negative health outcomes among nearby residents. Methods: Using a repeated-measures design, we assessed the impact of odor emissions on sleep duration and awakenings, important components and determinants of health and quality-of-life. Study participants from 16 residential communities in eastern North Carolina hosting swine ILOs, from 2003 to 2005, completed twice-daily diaries in which they rated the strength of hog odors and indicated whether they were asleep or awake per hour for two weeks. Simultaneously, a monitoring trailer placed in a central location in each community measured the atmospheric concentration of hydrogen sulfide (H2S). Subject-conditional fixed-effects regression models were used to estimate associations between two markers of swine ILO pollutant exposures (H2S and swine odor) and two self-reported sleep outcomes (nightly sleep duration and awakening from sleep). Results: Among 80 participants, nightly (across a 12-hour period) swine odor was associated with lower-nightly sleep duration (mean difference = -14.3 minutes, 95% confidence interval -25.0 to -3.3 minutes) compared to odor-free nights and detection of nightly hydrogen sulfide was associated with a 23% increased hazard of awakening (Hazard ratio = 1.23, 95% confidence interval 0.98 to 1.55) compared to nights with no detection of hydrogen sulfide. Conclusion: These results suggest that emissions reductions and odor abatement are important public health goals in designing policy and technology solutions to the problems of livestock production and waste management. Support (if any): This work was funded, in part, by the Intramural Program at the NIH, National Institute of Environmental Health Sciences (Z1AES103325-01).